Rethinking teacher training from an inclusive and community dialogical perspective - Morgado, Elsa Gabriel (2024)
This quantitative survey using a structured questionnaire with closed questions and a sample of 340 participants from 20 courses (bachelor's and master's degrees) at public higher education institutions in the Trás-os-Montes e Alto Douro region of the Portuguese university (University of Trás-os-Montes and Alto Douro) and polytechnic (Polytechnic Institute of Bragança) subsystem aims to list a group of proposals for reflection and future implementation that can fill or mitigate gaps and weaknesses identified in the disciplines of the curricula related to internships. The analysis of the data reveals indicators indicating the need for a (formal and conceptual) rethinking of inclusive intervention in the context of supervision in the field of teacher training. These indicators include problems with operating in a multifaceted educational setting, enhancing an interdisciplinary, integrated and inclusive approach, rearranging curriculum and reconsidering the functional profiles and competencies of teaching staff. Therefore, the construction of a professional culture that favors an integrative and inclusive approach through the assumption of a broad profile of professional competence capable of training the teacher in a multidimensional educational context is crucial. We evaluate the necessity of encouraging research of this type involving additional factors, populations and samples in order to enable the extrapolation of data and findings to a national level providing significance and technological foundations for decisions made within the context of public education policy.